Use of Shell-shape to discrimate between Brachidontes rodriguezii and Brachidontes purpuratus species (Mytilidae) in the transition zone of their distributions (South-western Atlantic) - Van Der Molen, Silvina (2013)
Mussels are important components of rocky shore assemblages throughout the world. Several Mytilid species are found as multilayered beds in the intertidal along the coasts of the South-western Atlantic. However, in contrast to the North communities in the Pacific and Atlantic, those of the Southwestern Atlantic are dominated by species of small size, locally named mejillines. These mid-intertidal beds attached to consolidated substrates are dominated by virtual monocultures of two small-sized species of Brachidontes: B. rodriguezii (d?Orbigny, 1842) and B. (= Perumytilus) purpuratus Lamarck, 1819, respectively distributed in the warm and cold temperate sectors of the South-western Atlantic; both coexisting in the transition zone between 40º and 44º S latitude. Nevertheless, there has been some confusion about the separation of Brachidontes rodriguezii and B. purpuratus, as well as about the boundaries of their distribution ranges in the Southwestern Atlantic. Here, on the basis of a morphogeometric analysis of shell morphology, we describe a feasible way for the identification of both species.